Dammarane-type triterpene extracts of Panax notoginseng root ameliorates hyperglycemia and insulin sensitivity by enhancing glucose uptake in skeletal muscle. Issue 2 (1st February 2017) - Kitamura, Kumiko; Takamura, Yusuke; Iwamoto, Taku; Nomura, Mitsuru; Iwasaki, Hideaki; Ohdera, Motoyasu; Murakoshi, Michiaki; Sugiyama, Keikichi; Matsuyama, Kazuki; Manabe, Yasuko; Fujii, Nobuharu L; Fushiki, Tohru
Abstract: Skeletal muscle is an important organ for controlling the development of type 2 diabetes. We discovered Panax notoginseng roots as a candidate to improve hyperglycemia through in vitro muscle cells screening test. Saponins are considered as the active ingredients of ginseng. However, in the body, saponins are converted to dammarane-type triterpenes, which may account for the anti-hyperglycemic activity. We developed a method for producing a dammarane-type triterpene extract (DTE) from Panax notoginseng roots and investigated the extract's potential anti-hyperglycemic activity. We found that DTE had stronger suppressive activity on blood glucose levels than the saponin extract (SE) did in KK- A y mice. Additionally, DTE improved oral glucose tolerance, insulin sensitivity, glucose uptake, and Akt phosphorylation in skeletal muscle. These results suggest that DTE is a promising agent for controlling hyperglycemia by enhancing glucose uptake in skeletal muscle. Graphical abstract: : DTM improved hyperglycemia.